2022
DOI: 10.1002/jsfa.12353
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic biofortification of forage crops with zinc and copper for enhancing nutritive potential: a systematic review

Abstract: Many developing countries are facing a silent increase in deficiency of micronutrients in forage crops that results in decreased levels of essential nutrients in animals. Micronutrients are essential not only for basic metabolic processes of forage crops but also for sustaining animal health. Forage productivity and quality are severely affected by soil micronutrients deficiencies, especially zinc and copper. This review summarizes the literature highlighting the significance of different methodologies used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Increasing production of crops with bioavailable micronutrients: a solution to reduce global malnutrition Malnutrition refers to diets that do not contain the proper amounts of nutrients, while hidden hunger refers to micronutrient deficiencies and affects almost one third of world population (Dwivedi et al, 2023). Recent scientific advances have focused on biotechnology and agronomic practices that may improve the nutritional quality of crops and contribute to combating malnutrition and ensure food security (Kumar et al, 2023;Singh Dhaliwal et al, 2023;.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing production of crops with bioavailable micronutrients: a solution to reduce global malnutrition Malnutrition refers to diets that do not contain the proper amounts of nutrients, while hidden hunger refers to micronutrient deficiencies and affects almost one third of world population (Dwivedi et al, 2023). Recent scientific advances have focused on biotechnology and agronomic practices that may improve the nutritional quality of crops and contribute to combating malnutrition and ensure food security (Kumar et al, 2023;Singh Dhaliwal et al, 2023;.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…
Editorial on the Research TopicIncreasing production of crops with bioavailable micronutrients: a solution to reduce global malnutrition Malnutrition refers to diets that do not contain the proper amounts of nutrients, while hidden hunger refers to micronutrient deficiencies and affects almost one third of world population (Dwivedi et al, 2023). Recent scientific advances have focused on biotechnology and agronomic practices that may improve the nutritional quality of crops and contribute to combating malnutrition and ensure food security (Kumar et al, 2023;Singh Dhaliwal et al, 2023;.This Research Topic compiles innovative research studies and review reports that gather up the most up-to-date information regarding the use of agronomic techniques that can be applied to various crops and result in higher bioavailability of micronutrients without compromising yield and quality of the final product.Yang et al investigated the selenium (Se) uptake and distribution dynamics in rice plants via Algal Polysaccharides-Selenium Nanoparticles (APS-SeNPs). Their hydroponic study, anchored in the Michaelis-Menten equation, revealed a notable Vmax of 13.54 mg g −1 root dry weight/hour for APS-SeNPs -7.69 and 2.23 times higher than selenite and selenate treatments, respectively.
…”
mentioning
confidence: 99%
“…The research results of [15] stated that adding manure to the soil can improve the physical properties of the soil. Organic fertilizer improves soil aggregates and increases soil nutrient content [11] [22]. If the physical properties of the soil are reasonable, it will make it easier for the roots of the mustard plant to grow in length.…”
Section: Root Lengthmentioning
confidence: 99%
“…According to Singh Dhaliwal et al [44] through the application of zinc, farmers can do agronomic fortification which will improve the quality as well as productivity of fodder crops. The problem of Zn deficiency is the most severe case among all micro-nutrients in India [45].…”
Section: Effects Of Zinc On Forage Crops and Fodder Cropsmentioning
confidence: 99%